2004
DOI: 10.3748/wjg.v10.i3.348
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of human gastric adenocarcinoma cells induced by β-ionone

Abstract: AIM:To investigate the effect of β-ionone on the growth and apoptosis of gastric adenocarcinoma cell line SGC-7901. METHODS:Using MTT, fluorescence dye (Hoechst-33258), transmission electron microscopy and the TUNEL assay, we examined growth and apoptosis of SGC-7901 cells treated with β-ionone at various concentrations (i.e. 25, 50, 100 and 200 µmol/L) for 24 h, 48 h. RESULTS:The growth of SGC-7901 cells was inhibited by β-ionone. Seven days after treatment with β-ionone at four concentrations, the inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 55 publications
0
28
0
3
Order By: Relevance
“…Apoptosis was induced in SGC-7901 cells at doses of 25-200lmol/l of b-ionone using the TUNEL assay and showed a dose-and time-dependent response. 10 Mo and Elson 12 also showed that b-ionone initiated apoptosis and, concomitantly arrested cells in the G1 phase of the cell cycle in human and murine tumor cells. In addition, b-ionone also affected the progression of metastasis in SGC-7901 cells 11 and B16 cells.…”
Section: Expression Of Apoptosis Bcl-2 and Bax In Mammary Cancer Tismentioning
confidence: 99%
See 3 more Smart Citations
“…Apoptosis was induced in SGC-7901 cells at doses of 25-200lmol/l of b-ionone using the TUNEL assay and showed a dose-and time-dependent response. 10 Mo and Elson 12 also showed that b-ionone initiated apoptosis and, concomitantly arrested cells in the G1 phase of the cell cycle in human and murine tumor cells. In addition, b-ionone also affected the progression of metastasis in SGC-7901 cells 11 and B16 cells.…”
Section: Expression Of Apoptosis Bcl-2 and Bax In Mammary Cancer Tismentioning
confidence: 99%
“…Discussion b-Ionone, a pure isoprenoid, has been shown to possess potent antiproliferative activity 9,13,17 and to induce apoptosis 10,12 in cancer cells. Liu's study 9 reported that b-ionone at doses of 25-200 lmol/l inhibited cell proliferation and DNA synthesis in human mammary cancer MCF-7 cells in a dose-dependent manner.…”
Section: Expression Of Apoptosis Bcl-2 and Bax In Mammary Cancer Tismentioning
confidence: 99%
See 2 more Smart Citations
“…Antitumor activities of β-ionone have been demonstrated in melanoma, breast cancer and chemical-induced rat carcinogenesis [13,22,32]. β-Ionone also inhibits the growth of various human cancer cells including breast and gastric tumor cells [8,21] and murine tumor cells [26]. Its exact mechanisms are not clear, but apoptosis is one of mechanistic actions of β-ionone on SGC-7901 gastric cancer cells, B16 murine tumor cells, and other cancer cells [8,21,26].…”
Section: Introductionmentioning
confidence: 99%